Zdravljenje napredovalega srčnega popuščanja z elektrostimulacijo srca na način resinhronizacije - Cvijić, Marta (Medicinski razgledi, 2011)
In view of inereased prevalence of heart failure and the persistent unacceptably high morbidity and mortality associaced with this condition despite current pharmacological treatments, novel therapeutic approaches have been sought. Cardiac resynchronization therapy offers proven benefit to patient with medically refractory symptomatic heart failure, severe left ventricular dysfunction (ejection fraction 120 ms). This treatment has the potential to improve survival and functional capacity, reduce hospital admissions, and promote left ventricular reverse remodeling. Although up to 30% of patients do nor attain symptomatic benefit. Factors associaies with poor response include inappropriate patient selection,suboptimal lead position, inadequate device setting and presence of myocardial scar. The aim of this article is to summarize the latest knowledge on the cardiac resynchronization therapy, from principles of the cardiac resynchronization therapy and its beneficial effects to different factors influence the response to cardiac resynchronization therapy.
Keywords: Heart Failure, Congestive; Srčno vzpodbujanje, umetno; Therapy; Srce, odpoved kongestivna; Cardiac Pacing, Artificial; Zdravljenje, izid; Instrumentation; srčno popuščanje; Methods; zdravljenje; Utilization; elektrostimulacija; Treatment Outcome